Modeling of heterogeneous catalytic recovery process of ketones - Skoretska, Ivanna; Beznosyk, Yuriy (Видавництво Львівської політехніки, 2017)
The article considers the mathematical model of the recovery reaction of cyclohexanole by the Meerwein- Ponndorf-Verley mechanism. The activity of the three catalysts in the presence of which the reaction of cyclohexanole recovery took place has been analyzed and selected the most active zeolite for further calculations. With the use of Mathcad 15.0 software the rate constants of investigated reaction has been calculated.
Keywords: Meerwein-Ponndorf-Verley mechanism; inverse problem of kinetics; rate constant; heterogeneous catalysis; zeolites